Peran Lembaga Alternatif Penyelesaian Sengketa dalam Menyelesaikan Sengketa Ekonomi Syariah - Mukharom Mukharom; Dharu Triasih; Dian Septiandani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractThe enactment of  Law Number 3 of 2006 concerning Religious Courts which in addition increases the authority of the Religious Courts in the field of Islamic economics, this makes the absolute authority of the Religious Courts. This research was carried out descriptively analytically, and the approach used was empirical juridical, so the data used in this study were primary data, and secondary data. The problem in this study is first, what is the role of alternative dispute resolution institutions in sharia economic dispute resolution; second, how are the challenges and obstacles of alternative dispute resolution institutions in resolving sharia economic disputes. The purpose of this study is to determine the extent of the role of alternative dispute resolution institutions in resolving sharia economic disputes. The results of the study illustrate that there are several factors underlying the development of Islamic economics in Indonesia: a.The large number of Muslims in Indonesia. b. Historically the Religious Courts deal with various Islamic civil laws. c. Religion Court Apparatus. d. Sharia economy is rapidly expanding. e. Build in concept in the community towards sharia economics. In addition, there are sharia economic constraints: a. Lack of government attention. b.The Religious Courts apparatus lacks understanding of economic activities and sharia financial institutions. c. The Religious Court has an inferior image that is difficult to remove; third, how are obstacles, challenges and efforts for Judges in the Religious Court; the obstacle for judges is the inadequate condition of the human resources of judges. The economic scope stated in Article 49 letter (i) of Law Number 3 of 2006 does not yet have a legal basis.Keywords: Dispute Resolution, Sharia Economy, Religious Courts  AbstrakBerlakunya Undang-Undang Nomor  3 Tahun 2006 tentang Peradilan Agama yang di dalamnya menambah kewenangan Peradilan Agama dalam bidang ekonomi syariah, hal ini menjadikan kewenangan absolut Pengadilan Agama. Penelitian ini dilakukan secara deskriptif analitis, dan pendekatan yang digunakan adalah yuridis empiris, sehingga data yang digunakan dalam penelitian ini yaitu data primer, dan data sekunder. Permasalahan dalam penelitian ini adalah Pertama, bagaimanakah peran lembaga alternatif penyelesaian sengketa dalam penyelesaian sengketa ekonomi syariah; Kedua, bagaimana tantangan dan hambatan lembaga alternatif penyelesaian sengketa dalam penyelesaian sengketa ekonomi syariah. Tujuan penelitian ini adalah untuk mengetahui sejauh mana peran lembaga alternatif penyelesaian sengketa dalam menyelesaikan sengketa ekonomi syariah. Hasil penelitian menggambarkan ada beberapa faktor yang melatarbelakangi perkembangan ekonomi syariah di Indonesia adalah: a. Besarnya jumlah umat Islam di Indonesia. b. Historis Peradilan Agama menangani berbagai hukum perdata Islam. c. Aparat Pengadilan Agama. d. Berkembang pesat ekonomi syariah. e. Konsep yang melekat (build in concept) di masyarakat terhadap ekonomi syariah. Selain itu, ada faktor penghambat ekonomi syariah: a. Kurangnya perhatian pemerintah. b. Aparat Peradilan Agama kurang memahami aktivitas ekonomi dan lembaga keuangan syariah. c. Peradilan Agama memiliki citra inferior yang sulit dihapus; Ketiga, bagaimana hambatan, tantangan dan upaya bagi para Hakim yang ada di lingkungan Pengadilan Agama; hambatan para hakim adalah keadaan sumber daya manusia dari para hakim yang belum memadai. Lingkup ekonomi yang tercantum dalam Pasal 49 huruf (i) Undang-Undang Nomor  3 Tahun 2006 belum memiliki dasar hukumnya.Kata Kunci: Penyelesain Sengketa, Ekonomi Syariah, Pengadilan Agama